Epidemiology of Antimicrobial Resistance Genes in Staphylococcus aureus Isolates from a Public Database from a One Health Perspective-Sample Origin and Geographical Distribution of Isolates - Francesca Zaghen; Valerio Massimo Sora; Gabriele Meroni; Giulia Laterza; Piera Anna Martino; Alessio Soggiu; Luigi Bonizzi; Alfonso Zecconi (MDPI AG, 2023)
Staphylococcus aureus are commensal bacteria that are found in food, water, and a variety of settings in addition to being present on the skin and mucosae of both humans and animals. They are regarded as a significant pathogen as well, with a high morbidity that can cause a variety of illnesses. The Centers for Disease Control and Prevention (CDC) has listed them among the most virulent and resistant to antibiotics bacterial pathogens, along with Escherichia coli, Staphylococcus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, Enterococcus faecalis, and Enterococcus faecium. Additionally, S. aureus is a part of the global threat posed by the existence of antimicrobial resistance (AMR). Using 26,430 S. aureus isolates from a global public database (NPDIB; NCBI Pathogen Detection Isolate Browser), epidemiological research was conducted. The results corroborate the evidence of notable variations in isolate distribution and ARG (Antimicrobial Resistance Gene) clusters between isolate sources and geographic origins. Furthermore, a link between the isolates from human and animal populations is suggested by the ARG cluster patterns. This result and the widespread dissemination of the pathogens among animal and human populations highlight how crucial it is to learn more about the epidemiology of these antibiotic-resistance-related infections using a One Health approach.